Cultural and linguistic adaptation of Bangla version of vitiligo impact scale-22 - Akhter, Sania; Sultana, Abida; Bhuiyan, Mohammed Saiful Islam; Jesmin, Afroza; Alam, Muhammad Jahidul; Lubna, Esrat Khan; Hossain, Marshad; Poudel, Hema (International Journal of Research in Medical Sciences, 2025)
Background: Vitiligo is known to have a major psychosocial effect on sufferers. “Vitiligo impact scale 22 (VIS 22)” is a newly developed specific scale to measure the quality of life (QoL) in vitiligo patients. As a psychometric evaluation of the Bangla version of VIS-22 has not yet been in Bangladesh. This study aimed to develop a culturally adapted Bangla version of English VIS-22 in Bengali-speaking vitiligo patients of Bangladesh. Methods: The original English version of the VIS-22 questionnaire was translated into Bangla following established cross-cultural procedures as recommended. The adapted Bangla version of VIS-22; and the Bangla version of SF-36 were administered and VASI was calculated. Results: The scale demonstrated a good internal consistency (Cronbach’s alpha=0.83) and significant test-retest reliability (by Pearson correlation 0.98 and by paired sample statistics 0.073). I-CVI for each item was 1. Construct validity assessing factor analysis-principal component analysis with the distribution of varimax rotation of VIS-22 Bangla ranged from 0.14 to 0.88 and six components were extracted. Criterion validity was assessed by comparing it with the VASI score which revealed Pearson correlation between VASI score and VIS-22 score was .30 which signifies a positive relationship. Correlation between the domains of SF-36 and VIS-22 Bangla was found between 0.45 to 0.60 in Pearson’s measurement. Conclusions: The adapted Bangla version of VIS-22 appears to be an acceptable, reliable, and valid instrument for measuring the QoL in Bengali-speaking patients of vitiligo.